The Lost Life of Ira Daniel Aldridge (Part 2) - Lindfors, Bernth (Text Matters: A Journal of Literature, Theory and Culture, 2013)
The sons of famous men sometimes fail to succeed in life, particularly if they suffer parental neglect in their childhood and youth. Ira Daniel Aldridge is a case in point—a promising lad who in his formative years lacked sustained contact with his father, a celebrated touring black actor whose peripatetic career in the British Isles and later on the European continent kept him away from home for long periods. When the boy rebelled as a teenager, his father sent him abroad, forcing him to make his own way in the world. Ira Daniel settled in Australia, married, and had children, but he found it difficult to support a family. Eventually he turned to crime and wound up spending many years in prison. The son of an absent father, he too became an absent father to his own sons, who also suffered as a consequence. Ira Daniel’s story is not just a case study of a failed father-son relationship. It also presents us with an example of the hardships faced by migrants who move from one society to another in which they must struggle to fit in and survive. This is especially difficult for migrants who look different from most of those in the community they are entering, so this is a tale about strained race relations too. And it takes place in a penal colony where punishments were severe, even for those who committed petty offences. Ira Daniel tried at first to make an honest living, but finally, in desperation, he broke the law and ended up incarcerated in brutal conditions. He was a victim of his environment but also of his own inability to cope with the pressures of settling in a foreign land. Displacement drove him to fail.